Fatty acid based transient nanostructures for temporal regulation of artificial peroxidase activity. Issue 32 (1st July 2019) - Ahmed, Sahnawaz; Chatterjee, Ayan; Das, Krishnendu; Das, Dibyendu
Abstract : Natural systems access transient high energy self-assembled structures for temporal regulation of different biological functions through dissipative processes. Abstract : Natural systems access transient high energy self-assembled structures for temporal regulation of different biological functions through dissipative processes. Compartmentalization within self-assembled structures is used by living systems to organize vital biochemical reactions that define cellular metabolism. Herein, we demonstrate a simple fatty acid based system where a redox active base (dimethylaminomethyl ferrocene, Fc-NMe2 ) acts as a countercation to access unique hexagonal compartments resulting in the formation of a self-supporting gel. An oxidizing environment helps in the dissipation of energy by convertingFc-NMe2 to oxidized waste and the gel autonomously undergoes transition to a sol. Hence, the system requires the addition of the fuelFc-NMe2 to access the temporal gel state. Notably, these transient compartments were able to temporally upregulate and downregulate hemin-catalyzed oxidation reactions mimicking peroxidase, a ubiquitous enzyme in extant biology. An order of magnitude variation in k cat values was observed with time and the chemical reaction persists as long as the gel state was present.